Effects of a micronutrient, glutamine, pre- and probiotic enriched liquid supplement on nutritional status and immunity of adults with HIV/AIDS : a pilot study - Kennedy, Roy Donovan (Stellenbosch : Stellenbosch University, 2012)
Thesis (Mnutr)--Stellenbosch University, 2003.